The use of acellular, fetal bovine dermal matrix for acute, full-thickness wounds - Rungsima Wanitphakdeedecha (2018)
Background: Skin substitutes may be used as part of the management of acute surgical wounds. The ideal skin substitute should be biocompatible, inexpensive, free of potential pathogens, easy to store, prepare, and utilize. Objective: To discuss the authors' direct clinical experience with an acellular, fetal bovine dermal matrix for the treatment of Mohs micrographic surgery (MMS) wound management. Methods: After the cutaneous malignancies were cleared by MMS, a sheet of the product was prepared according to the manufacturer's instructions, trimmed to fit the defect, and then secured to the wound to enhance contact with the wound bed. Results: Between June 2006 and July 2007, the product was used on a total of 10 wounds in 7 patients. Comorbidities included organ transplantation, Sezary syndrome with hepatitis C, and graft-versus-host disease. Seventy percent of the lesions were located on the lower extremities. The average defect area was 13.4 cm2 (range: 4.0-32.0 cm2). The dermal substitute was fully incorporated in 80% of defects and those that did not fully incorporate had exposed bone and tendon without the periosteum and peritendon, respectively. Conclusion: Skin substitutes may provide temporary coverage of acute, full-thickness surgical wounds allowed to heal by second intent. They may facilitate wound management with acceptable aesthetic outcomes. Alternate reconstructive options, however, such as cutaneous flaps, should be considered when there is exposed bone and/or tendon without their periosteum and/or peritendon. © 2008-Journal of Drugs in Dermatology. All Rights Reserved.